1975
DOI: 10.1136/ard.34.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA antibodies in systemic lupus erythematosus.

Abstract: Davis, P., Cunnington, P., and Hughes, G. R. V. (1975). Annals ofthe Rheumatic Diseases, 34,239-243. Double-stranded RNA antibodies in systemic lupus erythematosus. Antibodies to viral double-stranded RNA (ds RNA) have been found in 40% ofpatients with systemic lupus erythematosus (SLE) and 14-5 % of patients with rheumatoid arthritis. These antibodies were diagnostically more specific for SLE than those directed against artificial polynucleotides, poly I: C and poly A: U. Although not disease specific, high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…4o). Autoantibodies to dsRNA, as well as dsDNA, have been detected in patients with SLE 61,62 . However, it is unclear whether FH suppression is a cause or consequence of increased IFN signalling, as Fh1 can also be inhibited by IFNβ stimulation in BMDMs (Extended Data Fig.…”
Section: Articlementioning
confidence: 99%
“…4o). Autoantibodies to dsRNA, as well as dsDNA, have been detected in patients with SLE 61,62 . However, it is unclear whether FH suppression is a cause or consequence of increased IFN signalling, as Fh1 can also be inhibited by IFNβ stimulation in BMDMs (Extended Data Fig.…”
Section: Articlementioning
confidence: 99%
“…Suzuki et al found that phospholipid scramblase (phospholipid scramblase 1) induces fibrin turnover and increases cell-surface phosphatidylserine exposure, promoting the risk of thrombus (25). Doublestranded RNA antibodies have also been investigated in SLE, and RNA antibody levels have been found to be associated with disease activity (28). Interferon has been shown to act as an important regulator of SLE, and interferon lambda affects the immune system and inflammation dysregulation (29).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced FH activity has been shown in several diseases. In Systemic lupus erythematosus (SLE) patients, autoantibodies to double stranded RNA (dsRNA) are observed (Davis et al, 1975). Reduced ADAR1 RNA-editing activity results in dsRNA-mediated interferon response.…”
Section: Fumaratementioning
confidence: 99%